Mathematical communication ability viewed from mathematical anxiety in Team Assisted Individualization using Edmodo - Amalia, Dhea; Dwidayati, Nur Karomah (Department of Mathematics, Universitas Negeri Semarang, 2020)
This study aims to find out that mathematics learning using Edmodo-assisted TAI learning effectively affects students 'mathematical communication skills and describes students' mathematical communication skills through Edmodo-assisted TAI learning in terms of mathematical anxiety. The method used in this study is a mixed-method with a sequential explanatory design. Data collection methods used were tests, observations, questionnaires, and interviews. This study's population were students in grade 8 from one of the State Junior High School in Semarang for the 2019/2020 school year, using a random sampling technique that selected two classes, namely 8A class students as the experimental class and 8B class students as the control class. The results showed that: (1) students' mathematical communication skills using the Edmodo-assisted TAI model exceeded minimum completeness criteria and classical completeness; (2) the mathematical communication skills of students who use the Edmodo assisted TAI model is better than the mathematical communication skills of students who use Edmodo assisted direct instruction learning; (3) students with a low level of mathematical anxiety can meet all indicators; (4) students with medium mathematical anxiety can meet five of the six indicators; (5) students with high mathematical anxiety are only able to meet four of the six indicators of mathematical communication skills.